Potentials and Challenges in Development of Vesicular Phospholipid Gel as a Novel Dermal Vehicle for Thymol - Sabina Keser; Zora Rukavina; Marica Jozić; Lea Pavlović-Mitrović; Magda Vodolšak; Kristina Kranjčec; Darija Stupin Polančec; Gordana Maravić-Vlahoviček; Jasmina Lovrić; Maja Šegvić Klarić; Željka Vanić (Pharmaceutics)
Background/Objectives: Thymol, one of the main compounds of thyme essential oil, has shown promising effects in treating various skin disorders owing to its anti-inflammatory, antimicrobial and antioxidative activities. Due to its limited solubility in water, thymol is commonly used in higher concentrations to achieve a suitable therapeutic effect, which can consequently lead to skin irritation. To overcome these limitations, we incorporated thymol into a vesicular phospholipid gel (VPG), a novel semisolid dermal vehicle consisting of highly concentrated dispersion of phospholipid vesicles (liposomes). Methods: Thymol was successfully loaded into two VPGs differing in bilayer fluidity, which were characterized for the physicochemical and rheological properties, storage stability, in vitro release, ex vivo skin permeability, in vitro compatibility with epidermal cells, wound healing potential, and antibacterial activity against skin-relevant bacterial strains. Results: High pressure homogenization method enabled preparation of VPG-liposomes of neutral surface charge in the size range 140–150 nm with polydispersity indexes below 0.5. Both types of VPGs exhibited viscoelastic solid-like structures appropriate for skin administration and ensured skin localization of thymol. Although both types of VPGs enabled prolonged release of thymol, the presence of cholesterol in the VPG increased the rigidity of the corresponding liposomes and further slowed down thymol release. Conclusions: Loading of thymol into VPGs significantly reduced its cytotoxicity toward human keratinocytes in vitro even at very high concentrations, compared to free thymol. Moreover, it facilitated in vitro wound healing activity, proving its potential as a vehicle for herbal-based medicines. However, the antibacterial activity of thymol against Staphylococcus aureus and methicillin-resistant S. aureus was hindered by VPGs, which represents a challenge in their development.